Entrepreneurship - Practice-Oriented Perspectives 2016
DOI: 10.5772/65641
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cognition on New Value Creation within the Institutional Theory Perspective

Abstract: This study aims to assess the efects of optimism and self-eicacy on entrepreneurs who intend to reform their market. Drawing on cognitive and institutional theory, the factors of optimism and self-eicacy were selected to beter understand the association between entrepreneurial cognition and opportunity creation. This is a qualitative, multicase study where six Turkish entrepreneurial irms in the process of reforming and redeining their markets through new value creation, were selected on the basis of purpose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…The literature survey of current studies (e.g. Al-Jubari, 2019; Alam et al , 2019; Muhammad et al , 2015; Sabah, 2016; Van Gelderen et al , 2008) on entrepreneurial intentions has indicated that they have used TPB as their baseline models.…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…The literature survey of current studies (e.g. Al-Jubari, 2019; Alam et al , 2019; Muhammad et al , 2015; Sabah, 2016; Van Gelderen et al , 2008) on entrepreneurial intentions has indicated that they have used TPB as their baseline models.…”
Section: The Conceptual Modelmentioning
confidence: 99%